Single-cell analyses define a continuum of cell state and composition changes in the malignant transformation of polyps to colorectal cancer - Becker, Winston R.; Nevins, Stephanie A.; Chen, Derek C.; Chiu, Roxanne; Horning, Aaron M.; Guha, Tuhin K.; Laquindanum, Rozelle; Mills, Meredith; Chaib, Hassan; Ladabaum, Uri; Longacre, Teri; Shen, Jeanne; et al. (Nature genetics, 2022)
To chart cell composition and cell state changes that occur during the transformation of healthy colon to precancerous adenomas to colorectal cancer (CRC), we generated single-cell chromatin accessibility profiles and single-cell transcriptomes from 1,000 to 10,000 cells per sample for 48 polyps, 27 normal tissues and 6 CRCs collected from patients with or without germline APC mutations. A large fraction of polyp and CRC cells exhibit a stem-like phenotype, and we define a continuum of epigenetic and transcriptional changes occurring in these stem-like cells as they progress from homeostasis to CRC. Advanced polyps contain increasing numbers of stem-like cells, regulatory T cells and a subtype of pre-cancer-associated fibroblasts. In the cancerous state, we observe T cell exhaustion, RUNX1-regulated cancer-associated fibroblasts and increasing accessibility associated with HNF4A motifs in epithelia. DNA methylation changes in sporadic CRC are strongly anti-correlated with accessibility changes along this continuum, further identifying regulatory markers for molecular staging of polyps. Single-cell ATAC-seq and RNA-seq profiling traces the transformation of healthy colon to precancerous adenomas to colorectal cancer (CRC). A large proportion of polyp and CRC cells show a stem-like phenotype.